Irritable bowel syndrome following infectious COVID-19: East Java, Indonesia, 2023 - Hanum, Aisyah Rizki Nirmala; Illahika, Anung Putri; Santoso, Aktaruddin Arief; Putra, Probo Yudha Pratama (Intelektual Pustaka Media Utama, 2024)
Irritable bowel syndrome (IBS) is a functional disorder that causes chronic abdominal pain without a known cause. It is a common, chronic gastrointestinal (GI) motility disorder with bothersome symptoms that often lower quality of life and activity. In addition, Patients and healthcare facilities also face significant financial costs. COVID-19 directly damages the digestive system and alters the complex interaction of physical, mental, and social factors that cause digestive problems. SARS-CoV-2 survivors in personal isolation will be examined for IBS prevalence. The dates of this descriptive cross-sectional study are January through April 2023. Rome IV criteria and an online questionnaire were used to confirm the diagnosis of IBS. The principal location where polls have been sent is East Java, Indonesia. The 96 COVID-19 survivors aged 18–60 of both genders was included during self-quarantine. There were 59 females (61.46%) and 37 males (38.54%). The prevalence of IBS was discovered to be 19 (19.79%) among a total of 96 patients. This could be because self-quarantined people have more stable living conditions than hospitalized people. Based on these findings, it is suggested that future research consider gender as the primary proxy for identifying irritable bowel syndrome (IBS).